The Malabsorption syndrome versus Celiac disease: A diagnostic reappraisal - Beseda, Andrej; Bencat, Marián; Korinková, Lubica; Papanová, Janka; Rajcani, Julius (International journal of celiac disease, 2015)
The most frequent cause of malabsorption syndrome (MAS) in developed countries is the celiac disease (CD). There are two possible approaches for exact diagnostic of this disorder: in case of full blown clinical symptoms the golden standard is duodenal biopsy. When it shows classical mucosa lesions (Marsh type 3 mucosa atrophy of various grades), the diagnosis of CD is confirmed. However, if intraepithelial lymphocyte infiltration (IEL) and/or hyperplastic crypts can be seen in the absence of mucosa atrophy (Marsh type 1 and/or 2 lesions) only, it is reasonable to examine the serologic markers. The most frequent enzyme linked immunosorbent assay (ELISA) tests are: detection of tissue transglutaminase 2 antibody (anti-tTGase 2, especially of IgA class) and the deamidated gliadin peptide antibody (anti-DGP) assay. A simpler serological test, useful for screening, is the detection of anti-endomysium antibody (AEmA) by indirect fluorescent antibody (IFA) in monkey intestine or esophagus sections. This is reasonable to combine with the microdot test for anti-gliadin antibody (AGA), especially by using the endomysium/gliadin mosaic kit (Euroimmun). Taken together, at least three serological markers (anti-tTGase 2, anti-DGP and AGA) are highly specific for CD; their detection first (i.e. prior to duodenal biopsy) is recommended in children as well as in adults showing atypical, silent and or latent forms of CD. In both of them, serology represents a reliable non-invasive approach, which allows precise diagnosis with a probability of nearly 90 %. Another advantage of the non-invasive serological technic is that it can be easily repeated when following the outcome of gluten-free diet (GFD). Nevertheless, duodenal biopsy should be performed in any case, if the serology does not correlate with clinical symptoms. In such patients as well as in those revealing positive serology but negative and/or non-specific histology, immunogenetic typing should be performed in order to assess the expression of DQ2 [DQA*0501-DQB*0201] or DQ8 [DQA*0301-DQB1*0302] haplotypes of the human leukocyte antigen (HLA) class II region critical for the development of CD.
Keywords: malabsorpční syndromy; duodenoskopy; dospělí; Celiac Disease; Malabsorption Syndromes; sérologické testy; prediktivní hodnota testů; Biomarkers; celiakie; Serologic Tests; dítě; lidé; biologické markery; Duodenoscopes; Child; Humans; diferenciální diagnóza; Predictive Value of Tests; Adult; Diagnosis, Differential